Quantifying the Effect of Separator Thickness on Rate Performance in Lithium-Ion Batteries. Issue 3 (1st March 2022) - Horváth, Dominik V.; Tian, Ruiyuan; Gabbett, Cian; Nicolosi, Valeria; Coleman, Jonathan N.
Abstract : In addition to improving parameters such as energy density and stability, it is important to maximise rate performance in lithium-ion batteries. While much work has focused on rate-limiting factors associated with the electrodes, much less attention has been paid to the effect of the separator on rate-performance. Here we perform a quantitative study on the effect of separator thickness on the rate-performance of a model system of NMC-based half cells. By fitting experimental capacity vs rate curves, we measured the characteristic time associated with charge/discharge as a function of separator thickness, finding a roughly linear increase for separator thicknesses below ∼65 μ m. This behaviour is consistent with a simple physical model which shows the separator thickness dependence to be dominated by electrolyte resistance effects. The predictions of the model match the data extremely well with no adjustable parameters.